Discussion on "Sequential detection/isolation of abrupt changes" by Igor V. Nikiforov. Issue 3 (2nd July 2016) - Lai, Tze Leung; Tsang, Ka Wai
ABSTRACT: Professor Nikiforov has given a comprehensive overview of the quickest change detection/isolation problem in engineering. Following up on his discussion of asymptotically minimax properties of sequential generalized cumulative sum tests, we describe recent developments in postselection multiple testing and our work in relating them to sequential change detection/isolation in this big data era.